Effects of pyrolysis temperature and feedstock type on biochar characteristics pertinent to soil carbon and soil health: A meta‐analysis - Li, Lidong; Long, Amelia; Fossum, Britt; Kaiser, Michael (Soil use and management, 2023)
Biochar amendment to soil is utilized globally as an approach to enhance carbon storage and to improve soil functioning. However, biochar characteristics and related improvements of soil functioning depend on biochar production conditions. Systematic evaluation of corresponding biochar characteristics is needed for more targeted and efficient biochar application strategies. Herein, we systematically review the effects of biochar pyrolysis temperature (175–950°C) and feedstock (corn stover, switchgrass and wood) on selected biochar characteristics (carbon content, H/C ratio, nitrogen content, pH, specific surface area, ash content and pore volume). These specific characteristics were selected as being pertinent to soil organic carbon sequestration and soil health improvement. Despite numerous studies on these topics, few have numerically quantified the effects of pyrolysis temperature. Our results show that high pyrolysis temperature (>500°C) increased carbon content and pore volume for wood biochar compared with low pyrolysis temperature (≤500°C). The high pyrolysis temperature decreased the H/C ratio and nitrogen content but increased pH, specific surface area and ash content regardless of feedstock. Compared with corn stover biochar and switchgrass biochar, wood biochar had higher carbon content and larger specific surface area but lower nitrogen and ash contents regardless of pyrolysis temperature. The higher biochar carbon content might be derived from higher lignin and cellulose contents of wood feedstock. Wood feedstock had 76%–109% more lignin and 27%–47% more cellulose than corn stover and switchgrass. Corn stover biochar had higher pH, and switchgrass biochar had larger pore volume than wood biochar. Our study indicates that the targeted production of biochar with specific characteristics can be facilitated by the selection of pyrolysis temperature and feedstock type. For amending soil with biochar, more operationally defined biochar production conditions and feedstock selection might be a way forward to wider acceptance and better predictability of biochar performance under field conditions.